(Don't) fear the bad leader: three influential myths about bad leadership - Metz, Rudolf (Frontiers in Political Science, 2025)
IntroductionScholarship on bad leadership remains dominated by leader-centric paradigms that overstate the explanatory power of individual traits while neglecting the relational and identity-based processes that sustain harmful authority. This study challenges three influential myths: that bad leadership stems solely from leader pathology, that followers are passive conformists, and that support arises from psychological similarity between leaders and followers.MethodsThrough a critical and conceptual review of political science and social psychology literature, the study integrates conceptual and empirical findings to reassess prevailing assumptions about bad leadership and followership.ResultsThe analysis reveals that bad leadership is not a deviation from normal leadership but an expression of its underlying dynamics. Harmful leadership emerges through interactive processes among leaders, followers, and permissive environments. Followers are not merely obedient or trait-aligned individuals; rather, they actively co-produce legitimacy through engaged followership based on identification and identity leadership. Individual-level dispositions such as authoritarianism, populism, or dark personality traits influence leader tolerance primarily within the framework of group identity and ideological alignment.DiscussionThe findings challenge simplistic narratives of deviance and emphasize the central role of shared identity, group prototypicality, and affective polarization in shaping moral judgment and political legitimacy. Norm violations by in-group leaders are more likely to be tolerated or justified, particularly when perceived as benefiting the group. Future research should further explore the interaction between personality, identity, and institutional context in enabling or constraining bad leadership.